Acute Exacerbation of Interstitial Lung Disease in Adult Patients With Idiopathic Inflammatory Myopathies: A Retrospective Case-Control Study - Liang, Junyu; Cao, Heng; Ke, Yini; Sun, Chuanyin; Chen, Weiqian; Lin, Jin (Frontiers in Medicine, 2020)
Objective: This study aimed at clarifying the prevalence, risk factors, outcome and outcome-related factors of acute exacerbation of interstitial lung disease (AE-ILD) in patients with idiopathic inflammatory myopathy (IIM). Methods: Data of IIM patients who were admitted to the First Affiliated Hospital of Zhejiang University (FAHZJU) from September 2007 to September 2019 were retrospectively collected. And the IIM patients with AE-ILD formed the case group. In addition, age and sex matched IIM patients without AE-ILD were randomly selected to constitute the control group. A 1:2 case-control study and intragroup analysis were performed to identify risk factors for development of AE-ILD in IIM patients and unfavorable short-term outcome in AE-ILD patients through comparison, univariate and multivariate logistic regression analysis. Results: AE-ILD occurred in 64 out of 665 IIM patients (9.6%) with a short-term mortality rate of 39.1%. And the 64 IIM patients with AE-ILD formed the case group. Besides, 128 age and sex matched IIM patients without AE-ILD were randomly selected to constitute the control group. The retrospective case-control study revealed that elevated on-admission disease activity (P<0.001), lower percent-predicted diffusing capacity of the lung for carbon monoxide (DLCO%, P=0.013) and diagnosis of clinically amyopathic dermatomyositis (CADM, P=0.007) were risk factors for development of AE-ILD in IIM patients. The following intragroup analysis indicated that elevated on-admission disease activity (P=0.008) and bacterial infection (P=0.003) were significantly correlated with the unfavorable short-term outcome of patients complicated with AE-ILD. In addition, combined use of steroid and disease modifying antirheumatic drugs (DMARDs, P=0.006) was found to significantly reduce the short-term mortality in IIM patients with AE-ILD. Conclusion: AE-ILD is a less frequent but fatal complication in IIM patients with elevated on-admission disease activity, lower DLCO% and diagnosis of CADM working as risk factors, indicating the potential roles of autoimmune abnormality and hypoxia in development of AE-ILD. Elevated on-admission disease activity and bacterial infection could predict unfavorable short-term outcome of IIM patients with AE-ILD. A therapeutic regimen of steroid and DMARDs was found to reduce short-term death in these patients.